South African Biotechnology Initiatives: The Planning and Financing Perspective - Ofir, Z. (International Service for National Agricultural Research, 2001)
Africa is extraordinarily poor. A comparison of the wealth of its people with that of other continents reveals a shocking picture of a continent in the grip of poverty and stunted growth. Yet it has a wealth of natural resources that are not tapped by its own people to develop the continent economically. It is safe to say that most of the rest of the world cares about Africa only when it furthers their own interests. Economic colonization is as destructive as physical colonization and it is up to Africans to ensure the continent does not perish as its minerals, plants and animals are taken from it with little benefit to its own people. Visionary, accountable leaders — willing to take bold and hard decisions to create an environment conducive to industrial development — and excellent scientists, engineers and technologists who can utilize the continent's indigenous resources are needed to put Africa on the road to economic growth. For example, the development of indigenous industries capable of manufacturing and exporting refined products and processes rather than raw materials, should be a focus.